2002
DOI: 10.1051/0004-6361:20020506
|View full text |Cite
|
Sign up to set email alerts
|

Doppler imaging of stellar surface structure

Abstract: Abstract. We present eight Doppler images of UZ Librae from the years 1994, 1996, 1997, 1998 and 2000. These maps indicate a preferred temperature distribution from one year to the other and suggest preferred spot locations for at least the seven years of our observations. Two equatorial active regions appear facing towards and opposite the (unseen) companion star. A large and cool polar spot, with two or maybe three appendages extending down to a latitude of 40• -50• , is present and causes the long-term ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
(28 reference statements)
4
38
0
Order By: Relevance
“…The strongest emission occurs at photometric minimum, in accord with the presence of cool starspots on the rapidly rotating K giant (v sin i ≈ 90 km s −1 ; Bopp & Stencel 1981). Modelling photometric data, Olah et al (2002) found a surprisingly well-defined phase coherence of the light curve minima for eight consecutive years. If interpreted as being due to spots, two main spotted regions centered at approximately 90 • and 270 • longitude were present at all times between 1993 and 2001.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The strongest emission occurs at photometric minimum, in accord with the presence of cool starspots on the rapidly rotating K giant (v sin i ≈ 90 km s −1 ; Bopp & Stencel 1981). Modelling photometric data, Olah et al (2002) found a surprisingly well-defined phase coherence of the light curve minima for eight consecutive years. If interpreted as being due to spots, two main spotted regions centered at approximately 90 • and 270 • longitude were present at all times between 1993 and 2001.…”
Section: Introductionmentioning
confidence: 59%
“…Doppler images presented by Olah et al (2002) suggest prefered spot locations for at least seven years between 1993 and 2001 onto the surface of UZ Librae primary star. According to these maps, two equatorial active regions are facing towards and opposite the unseen companion star.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…per observing season): Korhonen et al (2007, FK Com, 24 maps from 1993, Vogt et al (1999, HR 1099 Visiting Astronomer, Kitt Peak National Observatory and National Solar Observatories, National Optical Astronomy Observatory, which is operated by the Association of Universities for Research in Astronomy, Inc. (AURA) under cooperative agreement with the National Science Foundation. from 1981 to 1992), , II Peg, 9 maps from 1992and 2001, LQ Hya, 9 maps from 1993 to 1999), Oláh et al (2002b, UZ Lib, 8 maps from 1994, Marsden et al (2007, IM Peg, 31 maps from 2003, Donati et al (2003, AB Dor, LQ Hya, HR 1099 and others. All of them are active stars and most of them are close binaries with their rotation period usually spun up by tidal forces.…”
Section: Introductionmentioning
confidence: 91%